Association between pulse wave velocity with other vascular markers and inflammation among young adults: an evidence-based review - Norizam Salamt; Amilia Aminuddin; Azizah Ugusman; Aini Farzana Zulkefli (Penerbit Universiti Kebangsaan Malaysia, 2018)
Studies evaluating the association between pulse wave velocity (PWV), a gold standard measurement of aortic stiffness and established markers of cardiovascular disease (CVD), with other established vascular markers or inflammation among young adult is still scarce. A systematic review of the literature was conducted to identify relevant studies on the association between PWV with other vascular markers or inflammation. Relevant articles from Ovid Medline, Science Direct and Scopus databases were explored between 2009 and March 2018. Original articles published in English measuring any correlation between carotid-femoral PWV (PWVcf) with either augmentation index (AIx), carotid intima media thickness (CIMT) or C-reactive protein (CRP) on young adult with age range between 18 and 45 years old were included. The literature search identified 21 potential articles to be reviewed, which meet all the inclusion criteria. Four articles investigated the correlation between PWVcf with CRP, however only two studies gave significant but weak correlations. As for CIMT, a single relevant article was found and the correlation was not significant. In conclusion, lack of association between PWV and other vascular markers and inflammation may suggest that these vascular markers have their own property in assessing vascular status. Thus, these markers should be measured independently for comprehensive assessment of future CVD risk.